Intra-individual relative deficits in visual memory to lateralize seizure onset in temporal lobe epilepsy - Sheldon, Sloane (Epilepsy Behav, 2020)
It is well established that presurgical neuropsychological assessment can assist in lateralizing and localizing focal epileptogenic regions. However, unlike verbal memory impairment, which is a robust and reliable finding in left temporal lobe epilepsy (LTLE) patients, nonverbal memory deficits are less consistently found among right TLE (RTLE) patients. This study aimed to determine whether memory assessment for spatial location in addition to visual content would differentiate RTLE and LTLE patients. We compared performances between 25 RTLE and 37 LTLE patients on the Wechsler Advanced Clinical Solutions-Faces (ACS-F) subscales (Faces I, Faces II, Content and Spatial), verbal-visual memory asymmetry scores, and IQ-visual memory difference scores. Results revealed no significant differences between RTLE and LTLE patients for any ACS-F memory score. By contrast, groups demonstrated significant differences in memory asymmetry scores (p=.007) and IQ difference scores (p=.006). Thus, visual memory scores in isolation failed to differentiate RTLE and LTLE groups; however, within-patient differences between visual memory and other cognitive abilities successfully differentiated the groups. These results highlight the importance of using an intra-individual model of neuropsychological assessment to identify relative weaknesses potentially associated with the epileptogenic region.